A strategy to reduce thermal expansion and achieve higher mechanical properties in iron alloys - Hao Lu; Chang Zhou; Yuzhu Song; Yuanpeng Zhang; Yiming Wu; Feixiang Long; Yonghao Yao; Jiazheng Hao; Yan Chen; Dunji Yu; J. Jakob Schwiedrzik; Ke An; et al. (Nature Communications)
Abstract Iron alloys, including steels and magnetic functional materials, are widely used in capital construction, manufacturing, electromagnetic technology, etc. However, they face the long-standing challenge of high coefficient of thermal expansion (CTE), limiting the applications in high-precision fields. This work proposes a strategy involving the in-situ formation of a nano-scale lamellar/labyrinthine negative thermal expansion (NTE) phase within the iron matrix to tackle this problem. For example, a model alloy, Fe-Zr10-Nb6, was synthesized and its CTE is reduced to approximately half of the iron matrix. Meanwhile, the alloy possesses a strength-plasticity combination of 1.5 GPa (compressive strength) and 17.5% (ultimate strain), which outperforms other low thermal expansion (LTE) metallic materials. The magnetovolume effect of the NTE phase is deemed to counteract the positive thermal expansion in iron. The high stress-carrying hard NTE phase and the tough matrix synergistically contribute to the high mechanical properties. The interaction between the slip of lamellar microstructure and the slip-hindering of labyrinthine microstructure further enhances the strength-plasticity combination. This work shows the promise of offering a method to produce LTE iron alloys with high mechanical properties.